Queer indigenous rhetorics: decolonizing the socio-symbolic order of Euro-American gender and sexual imaginaries - Allsup, Andrew (Kansas State University, 2015)
This thesis explores the rhetorical function of creative writing being written by queer/two-spirit identified indigenous authors. The rhetorical function being the way these stories politicize the various ways gender and sexuality were foundational tools of settler colonialism in de-tribalizing and assimilating indigenous folks. The literary perspective often elides politics in favor of deconstructing aspects of creative writing such as genre, syntax, and themes instead of the socio-political potential such works produce. The three works I examine all have something to teach rhetorical scholars about the need to politicize the socio-sexual and gendered imaginaries of settler colonialism in discourses of the founding fathers, manifest destiny, westward expansion, land purchase. statehood, American exceptionalism, democracy promotion, and many more. They fundamentally challenge rhetorics that posit static notions of American identity and/or purpose that represses the historical and ongoing genocide of indigenous culture and life. In this way, they intervene in the very notion of communicability itself within the socio-symbolic economy of settler colonialism and its attendant hetero-patriarchal gendered and sexual imaginaries.
Keywords: Queer theory; Indigenous studies; Native studies; Psychoanalysis; Rhetorical theory; Communication (0459); Comparative Literature (0295); Ethnic Studies (0631); Gender Studies (0733); GLBT Studies (0492); Literature (0401); Multicultural education (0455); Native American Studies (0740); Women's Studies (0453)